Configurational entropy of systems with non-additive lateral interactions - Nieto Quintas, Felix Daniel (2012)
The configurational entropy per site of a lattice gas model with non-additive interactions between adsorbed particles for square, triangular and honeycomb lattices is discussed in the present study. The model used here assumes that the energy which links a certain atom with any of its nearest-neighbors strongly depends on the state of occupancy in the first coordination sphere of that adatom. By means of Monte Carlo simulations in the canonical ensemble by following the algorithm of parallel tempering and the thermodynamic integration method the configurational entropy per site has been calculated. By analyzing the behavior of the configurational entropy per site, the different low-temperature-ordered phases are described. The dependency of the critical temperature of the system as a function of characteristic parameters of the model is established.